Pengembangan Media Audio Visual untuk Meningkatkan Keterampilan Menulis Teks Anekdot Siswa Kelas X Sekolah Menengah Atas Negeri 2 Lubuk Pakam - Adelia Rafita; Ridwan Syahputra; Rita Rita (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2026)
This study was conducted in response to the need for more engaging instructional media to improve students' anecdotal text writing skills, which remain relatively low under conventional classroom instruction. It aimed to develop an audio-visual learning media that is feasible and effective in improving anecdotal text writing skills among tenth-grade students of SMA Negeri 2 Lubuk Pakam. The study employed the Research and Development (R&D) method using the ADDIE model consisting of the Analysis, Design, Development, Implementation, and Evaluation stages. The population consisted of 394 students, while the sample included 36 students from class X-F. Research instruments included material expert validation sheets, media expert validation sheets, teacher response questionnaires, student response questionnaires, and an assessment of students' writing performance before and after the implementation of the developed media. The results showed that the developed media obtained validation scores of 92.67% and 80.67% from material experts, and 80% and 86% from media experts. Teacher responses reached 98%, while student responses reached 91%. In addition, students demonstrated improved anecdotal text writing performance after using the developed media. These findings indicate that the developed audio-visual media is highly feasible and effective for enhancing anecdotal text writing instruction.